(untitled) (Singaporean Journal of Business Economics and Management, 2012)
The shipping sector plays an important role in Indian economy. Almost 90 percent of the country’s trade by volume is conducted via sea and the country boasts of having the largest merchant shipping fleet among the developing nations. The Indian shipping industry not only transport national and international cargoes, but also provides various others facilities such as ship building, ship repairing, lighthouse facilities freight forwarding etc. with Globalization and liberalization the Indian shipping industry is all set to acquire new dimensions in terms of demand and infrastructural development. In order to resist stiff competition posed by foreign companies, the Indian shipping companies are striving to bring about rapid transformation. Therefore, the present paper examines measures initiated by the Indian Govt. to improve ports and Shipping Industry. The paper also focuses on the Key challenges faced by the Industry.